Flexural strength and fatigue properties of interfacial transition zone at the microscale. (October 2022) - Gan, Yidong; Zhang, Hongzhi; Liang, Minfei; Zhang, Yu; Schlangen, Erik; van Breugel, Klaas; Šavija, Branko
Abstract: In this study, the flexural strength and fatigue properties of interfacial transition zone (ITZ) were experimentally investigated at the micrometre length scale. The hardened cement paste cantilevers (150 × 150 × 750 μm 3 ) attached to a quartzite aggregate surface were prepared and tested under the monotonic and cyclic load using a nanoindenter. The measured flexural strength of the ITZ (10.49–14.15 MPa) is found to be one order of magnitude higher than the macroscopic strength of ITZ reported in literature. On the other hand, the fatigue strength of the ITZ is lower than that of bulk cement paste at same length scale, measured previously by the authors. The microscopic mechanical interlocking and the electrostatic interaction between aggregate surface and hydration products are thought to contribute to the bond strength of ITZ. This study provides an experimental basis for the development of multiscale analysis of concrete subjected to both static and fatigue loading.